Five new species of the New World genus Thyridopyralis Dyar, 1901 (Lepidoptera: Pyralidae, Galleriinae) - V. O. Becker (SHILAP)
Five new species of Thyridopyralis Dyar, 1901 from Brazil are described, including diagnosis and illustrations: Thyridopyralis bonita Becker, sp. n., T. leucophthalma Becker, sp. n., T. minor Becker, sp. n., T. proxima Becker, sp. n. and T. viridescens Becker, sp. n.; the range of T. gallaerandialis Dyar, 1901 is extended to Mexico and the Antilles (Guana Id., British Virgin Islands).